Ünnepi emlékkönyvek és tisztelgő tomusok: gondolatok egyetemtörténeti kötetekről - Virágos, Kálmán (Gerundium, 2023)
Jubilarian Academic Writing: Reflections on Commemorative Volumes of Institutional History. The present survey of both the theoretical ramifications and practical dilemmas of jubilarian academic writing attempts to look at the nature, conceptuality, and generic properties of commemorative writing as representative texts of institutional history in the ”groves of academe.” Particular attention is attributed to those personalized and self-contained volumes which have been earmarked as special gifts by peer-group members – most often colleagues and former students – in honour of professors and associate professors in the year of their jubilee, which also tends to be the year of their retirement. In the history of the Institute of English and American Studies, University of Debrecen, so far 7 Full Professors (listed in the chronological order of the year of their respective jubilees: László Országh [1993 and 2007: 2 vols.], István Pálffy [1999], Péter Egri [2002], Béla Korponay [1998 and 2008], Zoltán Abádi-Nagy [2010; 4 vols.], Donald E. Morse [2011 and 2012: 2 vols.], Zsolt Kálmán Virágos [2012; 2 vols.]) and 4 Associate Professors (Sarolta Kretzoi [2009], Csilla Bertha [2011], Béla Hollósy [2013], and Péter Pelyvás [2014]) have been the beneficiaries of commemorative volumes as special and honorary gifts. The author of the survey painstakingly documents the bibliographical details of all the respective essays published.